Reforming police stops in Spain: Evidence from the evaluation of new pilot projects - Arenas-García, Lorea (My University, 2015)
El trabajo analiza la gestión policial de la diversidad y la eficacia de las identificaciones policiales.
Keywords: Discriminación racial; Policía; Police stops; Discrimination